Spectral Modification by Diffraction and Scattering. (13th April 2010) - Tavassoly, M. Taghi; Dashtdar, Masoomeh; Amiri, Mohammad
Abstract : Different effects induce spectral changes, for example, correlation of source fluctuations, propagation of light, random changes in optical properties of a medium, diffraction and scattering from objects, and rough interfaces. We review the spectral changes that occur as a result of light diffraction from phase steps, and particularly we discuss the spectral changes in the neighborhood of phase singularities. We also review the redshift and blueshift in the spectra of the lights coherently and diffusely scattered from rough interfaces. In addition, we study the effects of roughness and incident angle on the spectral profiles of scattered lights in reflection and transmission modes.